NON-TECHNICAL SKILLS OF THE SCRUB PRACTITIONER: THE SPLINTS SYSTEM - Flin, Rhona; Mitchell, Lucy; McLeod, Bonnie (Operating Room Nurses Association of Canada Journal, 2014)
This article describes the nontechnical skill set, and behavioural rating tool, for scrub practitioners/nurses (e.g. perioperative registered nurses; operating room technicians) known as the Scrub Practitioners’ List of Intraoperative Non- Technical Skills or the SPLINTS system. The SPLINTS system was developed at the Industrial Psychology Research Centre of the University of Aberdeen, Scotland, by a research team comprising psychologists, scrub nurses, and a surgeon. Details of the system were presented, by Rhona Flin, at the ORNAC National and International Conference with IFPN, in Ottawa, in April of 2013. This article outlines the background of the research project and the method used to develop the SPLINTS system and suggests why it might be a valuable training and assessment tool for scrub practitioners in Canada.